Evaluation test method for hydrogen embrittlement of metal material in high-pressure hydrogen environment

The method assesses hydrogen embrittlement resistance of metal materials by simulating high-pressure hydrogen conditions, addressing the need for comprehensive evaluation and guiding safe use in high-pressure environments.

CN119223778APending Publication Date: 2024-12-31BAOSHAN IRON & STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310797189.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Current methods lack a comprehensive evaluation of hydrogen embrittlement performance of metal materials under high-pressure hydrogen environments, particularly for hydrogen pipelines and storage tanks, which is crucial for ensuring safety and durability.

Method used

A method involving sample preparation, bending, stress application, and exposure to a simulated hydrogen environment to assess crack extension, using hydrochloric acid solutions to simulate hydrogen conditions, with specific stress and time parameters to evaluate hydrogen embrittlement resistance.

Benefits of technology

Provides a detailed evaluation of hydrogen embrittlement resistance under varying hydrogen pressures, guiding the safe use and improvement of metal materials in high-pressure environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119223778A_ABST
    Figure CN119223778A_ABST
Patent Text Reader

Abstract

The invention discloses a hydrogen embrittlement evaluation test method for a metal material in a high-pressure hydrogen environment, which comprises the following steps: S1, preparing a sample, and treating the surface of the sample; s2, bending the sample to a corresponding curvature radius by adopting a bending tester, and cutting a prefabricated crack at the top of the sample; s3, after a stress tester is connected with the sample, carrying out stress loading on the sample by the bending tester; and S4, the sample subjected to stress loading is placed in a hydrogen environment, and if no crack propagation exists or the crack propagation amount is smaller than a threshold value, the material of the sample has the capacity of resisting hydrogen induced cracking. The method can evaluate the hydrogen embrittlement performance of the material in different hydrogen pressure environments, can analyze the influence of the influence factors on the high-pressure hydrogen embrittlement performance of the steel in combination with the process, alloy components and stress states of the steel, and provides guidance for hydrogen embrittlement evaluation of the steel serving in the high-pressure hydrogen environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a delayed fracture test method for metal materials in a high-pressure hydrogen environment, and more specifically to a hydrogen embrittlement evaluation test method for metal materials in a high-pressure hydrogen environment. Background Art

[0002] As a clean energy, hydrogen energy has a wide range of sources and has the advantages of high energy conversion rate, no pollution, zero emissions, storability, and renewability. It is an important direction for energy transformation and upgrading and has huge market potential. The entire life cycle of the hydrogen energy system includes hydrogen production, storage, transportation, and utilization. Among them, hydrogen storage and transportation connects upstream production and downstream end users, and is a key link in the middle. Long-term operation of hydrogen storage and transportation containers and pipelines in high-pressure, high-purity hydrogen environments can easily cause local plasticity reduction, accelerated crack propagation speed, and reduced durability, leading to hydrogen-induced cracking, hydrogen embrittlement, or fatigue damage. Solving the problem of high-pressure hydrogen embrittlement of materials is a prerequisite for the safe use of high-pressure hydrogen storage containers.

[0003] In the test of hydrogen embrittlement of materials, my country does not have a compatibility test standard for materials and high-pressure hydrogen. Some domestic hydrogen embrittlement test method standards can be used as references, such as GB / T24185-2009 "Test method for critical value of hydrogen embrittlement in steel", which can be applied to the test of environmental hydrogen embrittlement and internal hydrogen embrittlement; GB / T23606-2009 "Test method for critical value of hydrogen embrittlement in steel by step-by-step force method", which introduces the hydrogen embrittlement performance test of copper after heating in hydrogen atmosphere; GB / T8650-2006 "Evaluation method for hydrogen-induced cracking resistance of pipeline steel and pressure vessel steel" is a hydrogen-induced cracking test for pipeline steel and pressure vessel steel, and its main service environment is the corrosive environment of H2S aqueous solution. Internationally, ISO11114-4:2005 standard is specifically proposed for gas cylinders. In the EU region, such as the Austrian Hydrogen Research Center, the French Atomic Energy Research Center (French Atomic Energy Commission), the French Suez Gas Group, and the French Air Liquide Company have adopted this standard to conduct hydrogen embrittlement sensitivity tests on materials.

[0004] The hydrogen embrittlement test methods for metal materials can be roughly divided into two categories: one is used for preliminary material screening and rapid evaluation of whether the material can be used to manufacture hydrogen-exposed parts, such as disc test, hydrogen-induced cracking stress intensity factor threshold test, etc.; the other is used for in-situ testing of material mechanical properties to provide performance data for hydrogen-exposed parts design or material applicability evaluation, such as slow strain rate tensile test, fatigue crack growth rate test, fatigue life test, etc. Based on the actual service situation of metal materials, the present invention provides a method for evaluating hydrogen embrittlement of metal materials under high-pressure hydrogen environment, which has certain guiding significance for the evaluation of hydrogen embrittlement of metal materials, especially hydrogen pipeline steel. Summary of the invention

[0005] In view of the defects existing in the prior art, the purpose of the present invention is to provide a hydrogen embrittlement evaluation test method for metal materials in a high-pressure hydrogen environment, which can evaluate the hydrogen embrittlement performance of materials in different hydrogen pressure environments, and can combine these influencing factors with the process, alloy composition and stress state of the steel to analyze the influence of these influencing factors on the high-pressure hydrogen embrittlement performance of the steel, so as to provide guidance for the hydrogen embrittlement evaluation of steel serving in a high-pressure hydrogen environment.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] A method for evaluating hydrogen embrittlement of a metal material under a high-pressure hydrogen environment comprises the following steps:

[0008] S1. preparing a sample and treating the surface of the sample;

[0009] S2, using a bending tester to bend the sample to a corresponding radius of curvature, and cutting a prefabricated crack on the top of the sample;

[0010] S3, after connecting the stress tester to the sample, the bending tester applies stress to the sample;

[0011] S4. After stress loading, the sample is placed in a hydrogen environment. If there is no crack extension or the crack extension is less than a threshold value, the material of the sample has the ability to resist hydrogen-induced cracking.

[0012] Preferably, in step S1, the sample is cut into an arc shape by water cutting, and the arc of the sample is ≤90°, the arc length is ≤30cm, and the width is ≤15cm;

[0013] The alcohol ultrasonic method was used to remove the oil stains on the inner and outer surfaces of the sample, and then the sample was sanded to 1000# with sandpaper, and the edges were polished after grinding.

[0014] Preferably, in step S2, a prefabricated crack with a length of 0.25 mm is cut on the top of the sample by wire cutting.

[0015] Preferably, in step S3, the strain gauge on the stress tester is pasted to the top center of the sample so that the center of the strain gauge is aligned with the top center of the sample, and the stress tester is calibrated to zero.

[0016] Preferably, in step S3, the bending test machine performs stress loading on the sample specifically including:

[0017] The sample is placed in the fixture of the bending tester, and the stress T1 is loaded on the sample using the stress loading bolts on the bending tester. Then, the stress T2 is loaded on the top of the sample using the top stress loading bolts on the bending tester.

[0018] Preferably, the stress T1 is 0.05TS-1.00TS, and the calculation formula of the stress T2 is T2=60*TS / 950, where TS is the tensile strength of the sample, in MPa.

[0019] Preferably, the hydrogen environment in step S4 is specifically:

[0020] Hydrochloric acid solutions of different concentrations were used to simulate the hydrogen environment in which the material was in service.

[0021] Preferably, the relationship between the concentration C of the hydrochloric acid solution and the hydrogen pressure P in the material service environment is:

[0022] C=0.02+P / 300, the unit of C is mol / L, the unit of P is MPa.

[0023] Preferably, after the stress is applied, the sample is placed in the hydrogen environment for 1000 hours and then the sample is taken out;

[0024] The threshold value of the crack extension amount is 0.25 mm.

[0025] The present invention provides a method for evaluating hydrogen embrittlement of metal materials under high-pressure hydrogen environment. Starting from the material stress state and service environment, the stress and service environment can be combined to obtain the hydrogen embrittlement performance of steel under different hydrogen pressure conditions and clarify the hydrogen embrittlement risk of steel. The present invention can simulate the hydrogen embrittlement resistance of steel under different hydrogen pressure conditions, clarify the applicability and hydrogen embrittlement risk of steel under different hydrogen pressure conditions, and provide guidance and direction for improving the hydrogen embrittlement resistance of steel and its safe use. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic flow chart of a hydrogen embrittlement evaluation test method for metal materials under a high-pressure hydrogen environment of the present invention;

[0027] Figure 2 It is a schematic diagram of a bending test machine in a hydrogen embrittlement evaluation test method for metal materials under a high-pressure hydrogen environment of the present invention. DETAILED DESCRIPTION

[0028] In order to better understand the above technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0029] Combination Figure 1 As shown, the present invention provides a method for evaluating hydrogen embrittlement of metal materials in a high-pressure hydrogen environment, comprising the following steps:

[0030] S1. Prepare samples and process the surface of samples, including:

[0031] The sample was cut into an arc shape by water cutting, the arc of the sample was ≤90°, the arc length was ≤30cm, and the width was ≤15cm;

[0032] Use alcohol ultrasound for 15 minutes to remove oil stains on the inner and outer surfaces of the sample, then use sandpaper to grind to 1000#, grind the edges and polish for 10 minutes.

[0033] S2. Bend the sample to the corresponding radius of curvature using a bending tester according to the radius of the pipe / tank when the material is in service, and cut a prefabricated crack with a length of 0.25 mm on the top of the sample using a wire cutting method.

[0034] S3. Use strong glue to stick the strain gauge on the stress tester to the top center of the sample, making sure that the center of the strain gauge is aligned with the top center of the sample, and then calibrate the stress tester to zero to ensure that the stress is zero at this time. The bending tester applies stress to the sample, specifically including:

[0035] The sample is placed in the fixture of the bending test machine, and the stress loading bolt on the bending test machine is used to load the sample with stress T1, and then the top stress loading bolt on the bending test machine is used to load the top of the sample with stress T2.

[0036] Stress T1 is 0.05TS~1.00TS, and the stress magnitude is determined according to the bending stress of the material. The calculation formula of stress T2 is T2=60*TS / 950, and TS is the tensile strength of the sample in MPa.

[0037] S4. Place the stress-loaded sample in a hydrogen environment for 1000 hours and then take it out. If there is no crack extension or the crack extension is less than the threshold value of 0.25 mm, it is considered that the sample material has passed the test and the sample material has the ability to resist hydrogen-induced cracking.

[0038] The specific hydrogen environment is:

[0039] Based on the principle that the hydrogen charging speed of acidic solution is higher than that of gaseous hydrogen environment, hydrochloric acid solutions of different concentrations are used to simulate the hydrogen environment of the material during service, and the acidic solution environment replaces the hydrogen environment with a speed higher than that of gaseous hydrogen.

[0040] The relationship between the concentration C of the hydrochloric acid solution and the hydrogen pressure P in the material service environment is:

[0041] C=0.02+P / 300, the unit of C is mol / L, the unit of P is MPa.

[0042] Combination Figure 2 As shown, the bending testing machine mainly includes a fixture 1, a stress loading bolt 2, a strain gauge 3, a stress tester 4 and a top stress loading bolt 5.

[0043] The present invention aims to provide an in-situ hydrogen embrittlement evaluation test method for metal materials such as hydrogen pipelines and hydrogen storage tanks serving in high-pressure hydrogen environments, and is also applicable to metal materials in other high-pressure hydrogen environments. The present invention can be used to analyze the hydrogen embrittlement performance of materials under different hydrogen pressure environments, and can be combined with the process, alloy composition and stress state of steel to analyze the influence of these factors on the high-pressure hydrogen embrittlement performance of steel. The present invention can provide guidance for the hydrogen embrittlement evaluation of steel serving in high-pressure hydrogen environments.

[0044] The present invention mainly takes high-pressure hydrogen transmission pipeline steel and hydrogen storage tanks as research objects, and is also applicable to other metal materials.

[0045] Example 1

[0046] In this embodiment 1, 4130X is used as the test sample, and the specific operation is as follows:

[0047] S1. Sample preparation: Cut the sample by water cutting. The sample is in arc shape. The sample size is arc ≤ 90°, arc length ≤ 30 cm, and width ≤ 15 cm.

[0048] S2. Sample processing: The inner and outer surfaces of the sample were cleaned of surface oil by alcohol ultrasonic treatment for 15 minutes, and then sanded to 1000# with sandpaper, and the edges were polished for 10 minutes after sanding;

[0049] S3. Sample bending: The diameter of the 4130X hydrogen storage cylinder is 406mm, and it is bent with a curvature radius of 203mm using a bending tester;

[0050] S4, edge crack processing: use wire cutting method to cut a 0.25mm pre-crack on the top;

[0051] S5. Strain gauge installation: Use strong glue to stick the strain gauge to the center of the sample, make sure the center of the strain gauge is aligned with the center of the sample, and then connect it to the stress tester and return it to zero;

[0052] S6. Sample installation: Place the sample in the fixture and use the stress loading bolt to load the stress. The measured 4130X deflection stress T1 is about 0.4TS. TS is the tensile strength of the sample, which is 732Mpa in Mpa. Therefore, 0.4TS stress is applied to the sample.

[0053] S7, stress correction: connect the strain gauge to the stress tester, calibrate and balance it to ensure that the stress is zero at this time;

[0054] S8, top stress loading: Use the top stress loading bolt to stress load the top of the sample, the stress T2 calculation formula is T2 = 60*TS / 950, and the T2 value is 46.2Mpa;

[0055] S9, sample hydrogen environment setting: 4130X hydrogen pressure is set to 90Mpa, then the hydrochloric acid concentration of the simulated solution is C, which is calculated to be 0.32mol / L;

[0056] S10, Hydrogen embrittlement evaluation: After loading, place the sample in a simulated hydrogen environment for 1000 hours, then take out the sample, observe and measure the sample cracks. If the processing cracks do not extend, the sample passes this test.

[0057] Test materials TS / Mpa T1 / Mpa T2 / Mpa P / Mpa C / mol / L Crack extension / mm 4130X 732 293 46.2 90 0.32 0

[0058] Example 2

[0059] In this embodiment 2, SUS316L is used as the test sample, and the specific operation is as follows:

[0060] S1. Sample preparation: Cut the sample by water cutting. The sample is in arc shape. The sample size is arc ≤ 90°, arc length ≤ 30 cm, and width ≤ 15 cm.

[0061] S2. Sample processing: The inner and outer surfaces of the sample were cleaned of surface oil by alcohol ultrasonic treatment for 15 minutes, and then sanded to 1000# with sandpaper, and the edges were polished for 10 minutes after sanding;

[0062] S3. Sample bending: The diameter of the SUS316L hydrogen storage cylinder is 500mm, and it is bent with a curvature radius of 250mm using a bending test machine;

[0063] S4, edge crack processing: use wire cutting method to cut a 0.25mm pre-crack on the top;

[0064] S5. Strain gauge installation: Use strong glue to stick the strain gauge to the center of the sample, make sure the center of the strain gauge is aligned with the center of the sample, and then connect it to the stress tester and return it to zero;

[0065] S6. Sample installation: Place the sample in the fixture and use the stress loading bolt to load the stress. The measured SUS316L destressing stress T1 is about 0.5TS. TS is the tensile strength of the sample, which is 488Mpa in Mpa. Therefore, 0.5TS stress is applied to the sample.

[0066] S7, stress correction: connect the strain gauge to the stress tester, calibrate and balance it to ensure that the stress is zero at this time;

[0067] S8, top stress loading: Use the top stress loading bolt to stress load the top of the sample, the stress T2 calculation formula is T2 = 60*TS / 950, and the T2 value is 30.9Mpa;

[0068] S9, Sample hydrogen environment setting: S316L hydrogen pressure is set to 70Mpa, then the hydrochloric acid concentration of the simulated solution is C, which is calculated to be 0.26mol / L;

[0069] S10, Hydrogen embrittlement evaluation: After loading, place the sample in a simulated hydrogen environment for 1000 hours, then take out the sample, observe and measure the sample cracks. If the processing cracks do not extend, the sample passes this test.

[0070] Test materials TS / Mpa T1 / Mpa T2 / Mpa P / Mpa C / mol / L Crack extension hmm SUS316L 488 244 30.9 70 0.26 0

[0071] Example 3

[0072] In this embodiment 3, X56 is used as the test sample, and the specific operation is as follows:

[0073] S1. Sample preparation: Cut the sample by water cutting. The sample is in arc shape. The sample size is arc ≤ 90°, arc length ≤ 30 cm, and width ≤ 15 cm.

[0074] S2. Sample processing: The inner and outer surfaces of the sample were cleaned of surface oil by alcohol ultrasonic treatment for 15 minutes, and then sanded to 1000# with sandpaper, and the edges were polished for 10 minutes after sanding;

[0075] S3. Sample bending: X56 hydrogen pipeline steel with a diameter of 300 mm is bent with a curvature radius of 150 mm using a bending test machine;

[0076] S4, edge crack processing: use wire cutting method to cut a 0.25mm pre-crack on the top;

[0077] S5. Strain gauge installation: Use strong glue to stick the strain gauge to the center of the sample, make sure the center of the strain gauge is aligned with the center of the sample, and then connect it to the stress tester and return it to zero;

[0078] S6. Sample installation: Place the sample in the fixture and use the stress loading bolt to load the stress. The X56 bending stress T1 is measured to be about 0.35TS. TS is the tensile strength of the sample, which is 490Mpa in Mpa. Therefore, 0.35TS stress is loaded on the sample.

[0079] S7, stress correction: connect the strain gauge to the stress tester, calibrate and balance it to ensure that the stress is zero at this time;

[0080] S8, top stress loading: Use the top stress loading bolt to stress load the top of the sample, the stress T2 calculation formula is T2 = 60*TS / 950, and the T2 value is 30.9Mpa;

[0081] S9, Sample hydrogen environment setting: X56 hydrogen pressure is set to 10Mpa, then the hydrochloric acid concentration of the simulated solution is C, which is calculated to be 0.06mol / L;

[0082] S10, Hydrogen embrittlement evaluation: After loading, place the sample in a simulated hydrogen environment for 1000 hours, then take out the sample, observe and measure the sample cracks. If the processing cracks do not extend, the sample passes this test.

[0083] Test materials TS / Mpa T1 / Mpa T2 / Mpa P / Mpa C / mol / L Crack extension / mm X56 490 172 30.9 10 0.06 0

[0084] Those skilled in the art should recognize that the above embodiments are only used to illustrate the present invention, and are not intended to limit the present invention. As long as they are within the spirit of the present invention, any changes or modifications to the above embodiments will fall within the scope of the claims of the present invention.

Claims

1. A method for evaluating hydrogen embrittlement of metal materials under high-pressure hydrogen environment, characterized in that: The following steps are involved: S1. preparing a sample and treating the surface of the sample; S2, using a bending tester to bend the sample to a corresponding radius of curvature, and cutting a prefabricated crack on the top of the sample; S3, after connecting the stress tester to the sample, the bending tester applies stress to the sample; S4. After stress loading, the sample is placed in a hydrogen environment. If there is no crack extension or the crack extension is less than a threshold value, the material of the sample has the ability to resist hydrogen-induced cracking.

2. The method for evaluating hydrogen embrittlement of metal materials under high pressure hydrogen environment according to claim 1, characterized in that: In step S1, the sample is cut into an arc shape by water cutting, wherein the arc of the sample is ≤90°, the arc length is ≤30 cm, and the width is ≤15 cm; The alcohol ultrasonic method was used to remove the oil stains on the inner and outer surfaces of the sample, and then the sample was sanded to 1000# with sandpaper, and the edges were polished after grinding.

3. The method for evaluating hydrogen embrittlement of metal materials under high pressure hydrogen environment according to claim 1, characterized in that: In the step S2, a prefabricated crack with a length of 0.25 mm is cut on the top of the sample by wire cutting.

4. The method for evaluating hydrogen embrittlement of metal materials under high pressure hydrogen environment according to claim 1, characterized in that: In step S3, the strain gauge on the stress tester is pasted to the top center of the sample so that the center of the strain gauge is aligned with the top center of the sample, and the stress tester is calibrated to zero.

5. The method for evaluating hydrogen embrittlement of metal materials under high pressure hydrogen environment according to claim 4, characterized in that: In step S3, the bending test machine performs stress loading on the sample, specifically comprising: The sample is placed in the fixture of the bending tester, and the stress T1 is loaded on the sample using the stress loading bolts on the bending tester. Then, the stress T2 is loaded on the top of the sample using the top stress loading bolts on the bending tester.

6. The method for evaluating hydrogen embrittlement of metal materials under high pressure hydrogen environment according to claim 5, characterized in that: The stress T1 is 0.05TS to 1.00TS, and the calculation formula of the stress T2 is T2=60*TS / 950, where TS is the tensile strength of the sample, in MPa.

7. The method for evaluating hydrogen embrittlement of metal materials under high pressure hydrogen environment according to claim 1, characterized in that: The hydrogen environment in step S4 is specifically: Hydrochloric acid solutions of different concentrations were used to simulate the hydrogen environment in which the material was in service.

8. The method for evaluating hydrogen embrittlement of metal materials under high pressure hydrogen environment according to claim 7, characterized in that: The relationship between the concentration C of the hydrochloric acid solution and the hydrogen pressure P in the material service environment is: C=0.02+P / 300, the unit of C is mol / L, the unit of P is MPa.

9. The method for evaluating hydrogen embrittlement of metal materials under high pressure hydrogen environment according to claim 8, characterized in that: The stress-loaded sample is placed in the hydrogen environment for 1000 hours and then the sample is taken out; The threshold value of the crack extension amount is 0.25 mm.